2014
DOI: 10.1038/onc.2014.405
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species epigenetics identifies a critical role for VAV1 in SHH subgroup medulloblastoma maintenance

Abstract: The identification of key tumorigenic events in Sonic Hedgehog subgroup medulloblastomas (MBSHH) will be essential for the development of individualized therapies and improved outcomes. However, beyond confirmation of characteristic SHH-pathway mutations, recent genome-wide sequencing studies have not revealed commonly-mutated genes with widespread relevance as potential therapeutic targets. We therefore examined any role for epigenetic DNA methylation events in MBSHH using a cross-species approach to candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Fernandez-Zapico, et al ., demonstrated that epigenetic changes in the Vav1 gene, but not gene amplification, contributed to its aberrant expression in pancreatic cancer cell lines [ 69 ]. These results are further substantiated by a recent report indicating that Vav1 was identified by cross-species epigenetics to play a critical role in maintenance of Sonic Hedgehog (SHH) subgroup medulloblastoma tumors (MBSHH) [ 74 ]. This study identified widespread hypo-methylation of Vav1, leading to its elevated expression, as a conserved aberrant epigenetic event that characterizes the majority of MBSHH tumors and is associated with poor outcome in MBSHH patients.…”
Section: Why Is Vav1 Expressed In Cancer?supporting
confidence: 66%
See 2 more Smart Citations
“…Fernandez-Zapico, et al ., demonstrated that epigenetic changes in the Vav1 gene, but not gene amplification, contributed to its aberrant expression in pancreatic cancer cell lines [ 69 ]. These results are further substantiated by a recent report indicating that Vav1 was identified by cross-species epigenetics to play a critical role in maintenance of Sonic Hedgehog (SHH) subgroup medulloblastoma tumors (MBSHH) [ 74 ]. This study identified widespread hypo-methylation of Vav1, leading to its elevated expression, as a conserved aberrant epigenetic event that characterizes the majority of MBSHH tumors and is associated with poor outcome in MBSHH patients.…”
Section: Why Is Vav1 Expressed In Cancer?supporting
confidence: 66%
“…Several melanoma cell lines also express wild-type Vav1, including the highly metastatic BLM cells, although the level of protein expression was low and it was localized in the cell periphery near the plasma membrane [ 73 ]. Finally, a large screen of medulloblastomas identified widespread expression of Vav1 in the majority of specimens analyzed and Vav1 was demonstrated to play a critical role in medulloblastoma tumor maintenance, with Vav1 abrogation markedly reducing medulloblastoma growth [ 74 ].…”
Section: Vav1 Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, demethylation of VAV1 in the promoter region was shown to increase Vav1 expression in pancreatic cancer, and targeting Vav1 inhibited pancreatic cancer metastasis (Fernandez-zapico et al, 2005;Razidlo et al, 2015). Similarly, VAV1 gene is hypomethylated in medulloblastoma, leading to increased expression of Vav1 protein, which was correlated with the proto-oncogene MYCN amplification (Lindsey et al, 2014). Therefore, there is a need to elucidate epigenetic mechanisms regulating Vav expression, which can lead to novel therapeutic strategies.…”
Section: Targeting Vav1/2/3mentioning
confidence: 99%
“…Several recent studies have indicated that mutations in various domains of the Vav1 protein are present in human cancers such as adult T-cell leukemia/lymphoma (Kataoka et al, 2015), lung adenocarcinoma and squamous cell carcinomas (Campbell et al, 2016), and peripheral T-cell lymphomas (Abate, da Silva-Almeida et al, 2017). In addition, numerous studies have reported the unexpected expression of Vav1, normally found only in the hematopoietic system, in a variety of human cancers, such as neuroblastoma (Hornstein et al, 2003), lung (Lazer et al, 2009), breast (Lane et al, 2008;Sebban et al, 2013;Du et al, 2014;Grassilli et al, 2014), ovarian (Wakahashi et al, 2013), prostate (Kniazev Iu et al, 2003), esophageal (Zhu et al, 2017), and brain tumors (Lindsey et al, 2014). Notably, Vav1 expression was also identified in more than 50% of 95 examined pancreatic ductal adenocarcinoma (PDAC) tumor specimens (Fernandez-Zapico et al, 2005), a finding that was validated by Huang et al (2016).…”
Section: Introductionmentioning
confidence: 99%